2007
DOI: 10.1111/j.1365-246x.2007.03361.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper mantle beneath the Eger Rift (Central Europe): plume or asthenosphere upwelling?

Abstract: S U M M A R YWe present the first results of a high-resolution teleseismic traveltime tomography and seismic anisotropy study of the lithosphere-asthenosphere system beneath the western Bohemian Massif. The initial high-resolution tomography down to a depth of 250 km did not image any columnar low-velocity anomaly which could be interpreted as a mantle plume anticipated beneath the Eger Rift, similar to recent findings of small plumes beneath the French Massif Central and the Eifel in Germany. Alternatively, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 33 publications
4
65
0
Order By: Relevance
“…This result confirms a separate development of the Cadomian TBU block, an "undigested" microcontinent, which was only little affected by Variscan shortening, metamorphism and granitoid intrusion (Franke, 2000). A dense network of mobile and permanent seismic stations distributed in the western BM within the international BOHEMA experiment (Babuška et al, 2003) allowed Plomerová et al (2006) to delineate boundaries of the three mantle lithospheres characterized by different orientations of mantle A c c e p t e d M a n u s c r i p t olivine fabrics. The boundaries are marked by a "no P pattern", or by changes in the high-velocity directions (Fig.…”
Section: Accepted Manuscriptsupporting
confidence: 62%
See 1 more Smart Citation
“…This result confirms a separate development of the Cadomian TBU block, an "undigested" microcontinent, which was only little affected by Variscan shortening, metamorphism and granitoid intrusion (Franke, 2000). A dense network of mobile and permanent seismic stations distributed in the western BM within the international BOHEMA experiment (Babuška et al, 2003) allowed Plomerová et al (2006) to delineate boundaries of the three mantle lithospheres characterized by different orientations of mantle A c c e p t e d M a n u s c r i p t olivine fabrics. The boundaries are marked by a "no P pattern", or by changes in the high-velocity directions (Fig.…”
Section: Accepted Manuscriptsupporting
confidence: 62%
“…Therefore, we have firstly relocated the earthquakes that occurred in the region during [1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004]. Based on teleseismic tomography and seismic anisotropy, we have studied in detail the lithosphere-asthenosphere system beneath the western BM especially boundaries of the three mantle units, already located in a companion paper by Plomerová et al (2006). The aim of this paper is to discuss the causes of the earthquake swarms in the western BM (e.g., Neunhöfer and Hemmann, 2005).…”
Section: E-mail Address: Vbabuska@igcasczmentioning
confidence: 99%
“…USArray (www.usarray.org) or IberArray (http:// iberarray.ictja.csic.es/; Díaz et al, 2010) represent the largescale temporary networks, whereas for example TRANSALP (Lippitsch et al, 2003) or BOHEMA (Plomerová et al, 2007) belong to small-scale passive experiments in central Europe. Participants of the AlpArray project, the European collaborative geoscience initiative, deployed the largest network of temporary broadband (BB) stations ever perPublished by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal thickness of the lithosphere at the level of the 1 300 °C isotherm has been modelled to be 110-170 km, whereas the mechanical thickness is only 65-90 km (Babuška and Plomerová 1992;Goes et al 2000). Plomerová et al (2007) with Babuška and Plomerová (this volume) found clear differences in the orientations of seismic anisotropy in the three major tectonic units (Saxothuringian, Moldanubian and Teplá-Barrandian), but no signs for the existence of plume-like structures in the mantle. The region shows evidence for repeated magmatic phases before the Tertiary but most of the Eger Rift lavas erupted between 30 and 15 Ma both within the rift and on its NW flank (Todt and Lippolt 1975;Pilot et al 1984;Kaiser and Pilot 1986;Ulrych et al 2002).…”
Section: Geological Settingmentioning
confidence: 99%